Impact of ecological factors on nationwide supply chain performance - Tarofder, Arun Kumar; Haque, A. K. M. Ahasanul; Hashim, Nurhazirah; Azam, S. M. Ferdous (Cevre Koruma ve Arastirma Vakfi, 2019)
Environmental responsibility is an integrated part of responsible supply chain management and involves several steps.The objective of this study is to investigate the role of ecological factors in the supply chain. Therefore, this study examined the role of GDP growth rate, the degree of openess, the rate of exchange and balance of payment effect on foreign direct investment (FDI) and FDI effect on the supply chain. Different national and international frameworks and tools guide companies in their work with sustainability and environmental supply chain management. UN’s Global Compact is one of the main international frameworks. In this study, data were collected from Indonesian ecologists. Email addresses of Indonesian ecologists were collected and email was sent to them to get responses. Only one hundred email addresses were found of various ecologists. Therefore, the total sample size was one hundred. From total one hundred, sixty ecologists responded. Outcomes of the study show that increases in GDP growth rate, the degree of openness and balance of payment increases the nationwide supply chain performance. Decreases in GDP growth rate, the degree of openness and balance of payment decreases the nationwide supply chain performance. However, increases in the rate of exchange decrease the FDI growth rate which ultimately decreases the supply chain practices